Social relevance of public and private universities: teachers’ perspective - Vera Noriega, José Ángel; Rodríguez Carvajal, Claudia Karina; Bustamante Castro, Ivett Alejandra (Rastros Rostros, 2017)
Introduction: One of the current demands of Higher Education, both public and private, is quality. This concept is closely linked with social relevance, which refers to the role that Higher Education plays in society and what society expects from it. In this sense, a university system’s quality is the product of several factors and processes, amongst which the teacher appears as a subject of study, so as to analyze his perception about the social relevance of the institution. Methodology: From a descriptive research approach, we analyze the perception of 121 teachers from two Higher Education institutions in northwest Mexico, one public and one private. Surveys regarding the quality of the functions of the institution in which they work were carried out. These had categories proposed by De la Orden, Muñoz, López, Barberá and Ndabishibije, under the premise that Institutional quality should assess the coherence between the needs of society and those of the institution. Results: In both institutions teachers evaluate positively the relevance of the institution. Similarly, variability of results is observed between the two institutions. Conclusion: The research shows that the lack of diffusion or information about the different functions that the University fulfills influences the way in which teachers perceive these functions.